2019
DOI: 10.1155/2019/3921426
|View full text |Cite
|
Sign up to set email alerts
|

Dry Powder and Budesonide Inhalation Suspension Deposition Rates in Asthmatic Airway-Obstruction Regions

Abstract: Steroid inhalation is the standard bronchial asthma therapy and it includes powdered metered doses, dry powder, and nebulizer suspension. However, particle sizes vary widely. The research goal was to demonstrate that different budesonide administration forms and devices have various deposition rates in the airway obstruction region. Here, we compared relative inhalation therapy efficacies and identified therapies that delivered the highest drug doses to the airway obstruction region. Weibel's anatomy data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…To this end, we have focused on enhancing the lung pharmacokinetics by endowing our formulation with the ability to avoid natural clearance mechanisms inevitably encountered following the settlement on lung lumen. Multiple reports have demonstrated that nebulization provides markedly greater or more uniform deposition in human lungs compared to dry powder inhalation 52,53 . We here show that NTB‐NS can be aerosolized with a vibrating mesh nebulizer without perturbing the physicochemical properties that enable enhanced lung pharmacokinetics.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…To this end, we have focused on enhancing the lung pharmacokinetics by endowing our formulation with the ability to avoid natural clearance mechanisms inevitably encountered following the settlement on lung lumen. Multiple reports have demonstrated that nebulization provides markedly greater or more uniform deposition in human lungs compared to dry powder inhalation 52,53 . We here show that NTB‐NS can be aerosolized with a vibrating mesh nebulizer without perturbing the physicochemical properties that enable enhanced lung pharmacokinetics.…”
Section: Resultsmentioning
confidence: 67%
“…Multiple reports have demonstrated that nebulization provides markedly greater or more uniform deposition in human lungs compared to dry powder inhalation. 52,53 We here show that NTB-NS can be aerosolized with a vibrating mesh nebulizer without perturbing the physicochemical properties that enable enhanced lung pharmacokinetics. Of note, vibrating mesh nebulizers have been shown in clinical studies to provide superior lung deposition or therapeutic outcomes compared to jet nebulizers which have a longer history of clinical use.…”
Section: In Vivo Therapeutic Efficacy Of Locally Administered Ntb-ns ...mentioning
confidence: 83%
“…2 ) [ 23 ]. From the formulation point of view, estimation of budesonide particle size expands its usage in multiple dosage forms especially aerosol or nebulizer [ 24 26 ]. Also, particle size distribution in the dosage forms (suspension or aerosol) is typically associated with absorption rate and bioavailability.…”
Section: Resultsmentioning
confidence: 99%
“…From the percentage value for 3 µm ( Figure A1, blue line) we can get the mass of the particles with a diameter less than 3 µm, from which we get FPF < 3 µm as a percentage of the ED. This value has also been expressed by several publications recently [77,78], because in the sub-tracheal region of the lung-in the deep lung-mainly particles below 3 µm form deposits [79]; thus, when comparing the aerodynamic properties of the DPI formulations, the calculation of the deep lung deposit value is also expedient. It should be noted that in addition to the reported results, the FPF < 4.7 µm calculation is always performed as a control, which is exemplified in the literature [80].…”
Section: Discussionmentioning
confidence: 71%